A forgotten creed in the summer of rage. Issue 3 (29th July 2020) - Patterson, Stephen J.
Abstract: In the summer of 2020 America erupted in rage, protesting racism and age‐old inequalities. In the summer of rage, American churches will find their voice in an ancient creed preserved in Galatians 3:26‐28, arguably the first Christian creed.